Bridging social capital: a survey of race and ethnicity representation in the Instagram visuals of a public university - Maxwell, Jessica (Kansas State University, 2023)
This report is an examination of the association between college students’ use of university Instagram accounts and their bridging and bonding social capital. The analysis also gauges student perceptions of race and ethnicity diversity and representation in the Instagram accounts of higher education institutions, in addition to differences in social capital by race and ethnicity. Through a survey approach, the study explores the relationship between the use of Instagram, a popular social network site, and the connections users form within the university using the framework of the social capital theory. The assessment of these relationships was conducted by surveying students within the College of Education at Kansas State University. The findings have practical implications for higher-education institutions that want to more effectively attract and support students from underrepresented groups.
Keywords: Social media; Representation; Social capital